Blunt Traumatic Injury to the Superficial Femoral Artery in a Morbidly Obese Female: Case Report Using Endovascular Covered Stent Repair. (February 2021) - Weeks, Ahna H.; Grant, April A.; Sciarretta, Jason D.; Nguyen, Jonathan; Todd, S. Rob; Rajani, Ravi
Lower extremity vascular injuries following trauma are rare events that require prompt identification and management in order to prevent ischemia and limb loss. Endovascular approaches, rather than traditional open procedures, are increasingly used to treat a wide range of vascular disease. The use of endovascular repair for revascularization in the trauma setting is not routine but may provide an appealing alternative in select trauma patients and injuries. We present a case of successful endovascular repair with stent grafting of a superficial femoral artery intimal injury following a femur fracture in a 35-year-old morbidly obese female and review the current literature regarding the use of endovascular therapy in the trauma setting.